2017
DOI: 10.1111/cge.13019
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of patients with aniridia in Russian Federation broadens the spectrum of PAX6 mutations

Abstract: Congenital aniridia is a severe autosomal dominant congenital panocular disorder, mainly associated with pathogenic variants in the PAX6 gene. The objective of the study was to investigate the mutational and clinical spectra of congenital aniridia in a cohort of 117 patients from Russia. Each patient underwent detailed ophthalmological examination. From 91 unrelated families, 110 patients were diagnosed with congenital aniridia and 7 with WAGR syndrome (Wilms tumor, Aniridia, Genitourinary anomalies, and menta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 12 publications
2
35
0
1
Order By: Relevance
“…Further analysis of segregation of this SNV in pedigree showed proband's grandfather carried the variant and had no signs of aniridia. The deletion affecting PTC/NMD premature termination codon formation followed by mRNA degradation through the nonsense mediated decay pathway the PAX6 distal 3′-cis-regulatory region was found in a proband [2].…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Further analysis of segregation of this SNV in pedigree showed proband's grandfather carried the variant and had no signs of aniridia. The deletion affecting PTC/NMD premature termination codon formation followed by mRNA degradation through the nonsense mediated decay pathway the PAX6 distal 3′-cis-regulatory region was found in a proband [2].…”
Section: Resultsmentioning
confidence: 95%
“…A previously conducted molecular genetics study of a cohort of 110 patients from 84 unrelated Russian families with a clinical diagnosis of congenital aniridia revealed six single nucleotide variants out of canonical splicing site dinucleotides, which may affect splicing: five intronic (c.142−5T>G, c.142−14C>G, c.141+4A>G, c.1032+6T>G, c.682+4delA) and one missense variants (c.140A>G) [2]. Two more PAX6 sequence variants were newly identified later: one synonymous (c.174C>T) and one deep-intronic (c.142−64A>C) (unpublished data).…”
Section: Introductionmentioning
confidence: 99%
“…PTCs in this region are expected to escape NMD and they would result in truncated proteins with a possible dominant negative effect and more severe phenotypes [81,82]. However, within the region that was predicted to escape NMD, i.e., the last 50 bp from exon 12 and exon 13, there are no nonsense mutations reported aside from c.1183G>T (p.Gly395*) in the last nucleotide of exon 12, but with predicted mRNA missplicing [83], and all frameshift changes are predicted to cause C-terminal extensions [78].…”
Section: Premature Termination Codon (Ptc) Mutations-nonsense Framesmentioning
confidence: 99%
“…It is well accepted that the frameshift mutation c.879_880delCA (p.S294Cfs*46) can cause congenital aniridia, which leaded to a truncated protein. In reviewing previous literatures, we found that there are two frameshift mutations reported pathogenic at the same genome coordinate, which are c.879delC (p.Ser294Valfs*71) and c.879dupC (p.T293fsX47) (Vasilyeva et al., ; Villarroel et al., ). According to the ACMG STANDARD AND GUIDELINES 2015 (Richards et al., ), the frameshift variants at c.879 of PAX6 are pathogenic and its pathogenicity evidence grade PVS1 is high.…”
Section: Discussionmentioning
confidence: 81%